Ingredientele unei vieţi bune şi ale unui standard decent de viaţă, în România şi în Europa - Pop, Cosmina-Elena (Calitatea Vieții, 2008)
The way that people are defining their requirements for a qualitative life or for a decent standard of living, is affecting their evaluations, their perceptions and also their level of satisfaction on different life domains. This article proposes to describe the needs identified by Romanians in order to have “a good life” or “a decent standard of living”. The article is based on the data from two researches: Quality of Life Diagnosis (2006) and Standard Eurobarometer 67.1 (2007) and it is presenting the Romanians opinions in a comparison with the opinions of other Europeans from member or candidate countries of the European Union. Within the article, it was included a component regarding the evaluation of economic strain in the European households and the perception of causes for poverty, because these may contribute to establishing criteria for standard of living or for a good life. The last part of the article is referring to measures for improving the living conditions, as they are identified by Romanians within the research Quality of Life Diagnosis (2006).